THE EFFECT OF THE IMPLEMENTATION OF THE QUIZIZZ APPLICATION ON STUDENTS' CONCENTRATION DURING THE INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) SUBJECT EXAM IN GRADE 8 AT PGRI 2 CITANGKIL SMP, CILEGON CITY - Atu Sumiati; Kurniati Rahmadani; Desty Endrawati Subroto (Cakrawala Pedagogik, 2025)
Learning media that suits students' conditions and needs can increase exam concentration and learning motivation, so teachers need to know the media criteria that must be used so that students can like and accept them. Quizizz is one of the learning media in the form of quizzes. Quizizz can be chosen by teachers as a learning medium because it is game and technology based. The aim of this research is to describe the effect of using Quizizz media on exam concentration and learning motivation on persuasive text material. This research uses a quantitative approach, because the data presented is in the form of numbers and analyzed using statistical formulas. This research uses experimental research methods, with a true experimental design. The number of samples in this study was 30 students, divided into experimental and control classes. The instruments used were questionnaires and test sheets. The data collection techniques used were questionnaires and tests. Based on the results of research data analysis, the influence of the Quizizz application on exam concentration and learning motivation was 56%, while the remaining 44% was influenced by other variables or factors that were not rigorous, indicating that there was a significant difference in exam concentration and learning motivation between experimental class students and control, so it can be concluded that there is a positive influence of using Quizizz interactive media on exam concentration and learning motivation on persuasive text material.